Hardware embarcado para aquisição e análise de sinais vitais usando o protocolo de comunicação Modbus - Andrade, Luís Otávio Santos de (2016)
Computers network in the hospital environments are central topics of discussion on the use of systems applied to health care to ensure data capture of vital signs. This study aims at analyzing the data capture model of the proposed sensor node, using the Modbus protocol communication standard in the acquisition of multi-parametric information of biological signs of patients. The research was conducted with experimental purpose to characterize the ModBus protocol in the RS485 serial network. It was also performed a systematic review to support the choice of the data model and serial communication standard in wired networks. Thus, a sensor node prototype (PIC18F26K20) was built to capture body temperature and heart rate in the wired communication network in which the protocols CAN and ModBUS were tested. The data from the sensor nodes were subjected to capture tests and sending the data to the central node, and displayed on portable platform (Smartphones). It was also observed the bandwidth characteristics and quality of the obtained data. The systematic review showed a trend in the use of the CAN protocol as wired communication standard for HealthCare activities, the application used in the experiment presented limitations. However, after the experiment using the ModBus protocol, this was adequate and easy to implement applications in the hospital environment, having a low-cost platform as a solution to that area.